2016
DOI: 10.1371/journal.pone.0167381
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Thalamocortical Connectivity in Chronic Ketamine Users

Abstract: Disintegration in thalamocortical integration suggests its role in the mechanistic ‘switch’ from recreational to dysregulated drug seeking/addiction. In this study, we aimed to address whether thalamic nuclear groups show altered functional connectivity within the cerebral cortex in chronic ketamine users. One hundred and thirty subjects (41 ketamine users and 89 control subjects) underwent rsfMRI (resting-state functional Magnetic Resonance Imaging). Based on partial correlation functional connectivity analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 40 publications
(46 reference statements)
2
17
0
Order By: Relevance
“…For instance, cigarette smokers showed reduced connectivity between the thalamus and the dorsolateral PFC, and the strength of the dorsolateral PFC–thalamus connectivity was negatively associated with severity of nicotine dependence (Wang et al, ). Similar results were also shown in ketamine‐dependent individuals (Liao et al, ). In addition, thalamocortical neurons are essential for thalamocortical information transfer and regulation of arousal and sleep (Del Felice, Formaggio, Storti, Fiaschi, & Manganotti, ; Krone et al, ).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…For instance, cigarette smokers showed reduced connectivity between the thalamus and the dorsolateral PFC, and the strength of the dorsolateral PFC–thalamus connectivity was negatively associated with severity of nicotine dependence (Wang et al, ). Similar results were also shown in ketamine‐dependent individuals (Liao et al, ). In addition, thalamocortical neurons are essential for thalamocortical information transfer and regulation of arousal and sleep (Del Felice, Formaggio, Storti, Fiaschi, & Manganotti, ; Krone et al, ).…”
Section: Introductionsupporting
confidence: 85%
“…Previous neuroimaging studies observed structural and functional differences of thalamus between substance use disorder and healthy controls (Feil, Sheppard, Fitzgerald, Yücel, & Lubman, ). Several studies showed that reduced thalamic connectivity was associated with increased craving and other measures of severity of drug dependence (Liao et al, ; Wang et al, ). However, the implication of thalamocortical circuits in neural mechanisms of AD patients remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, few studies have examined changes in cerebral structure, activation and connectivity in chronic ketamine users (Hoflich et al, 2016; Liao et al, 2016; Wang et al, 2013), who frequently suffer comorbid depression (Chang et al, 2016). Women are more vulnerable than men to depression (Kessler, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Serious lower urinary tracts symptoms (increased urinary frequency, urgency, incontinence, hematuria, and dysuria) [14][15][16], gastritis and liver and kidney dysfunction [16,17] are also common in this population. Psychiatric disorders are often comorbid by ketamine include depression, which is remarkably prevalent among chronic ketamine users [18,19] [29]. However, it is still not clear if chronic ketamine intake is the cause or consequence of these brain alterations due to the cross-sectional design of these studies [28].…”
mentioning
confidence: 99%
“…A few neuroimaging studies revealed structural and/or functional abnormalities in the frontal regions in chronic users. For example, compared to controls ketamine users had less bilateral prefrontal grey matter [25], lower white matter integrity and more axon damage in the prefrontal regions [26,27], altered regional synchrony of metabolism in the precentral frontal gyrus and anterior cingulate cortex (ACC) [28] and altered resting state functional connectivity (RSFC) between thalamic nucleus and several cortical regions including the prefrontal area [29]. However, it is still not clear if chronic ketamine intake is the cause or consequence of these brain alterations due to the cross-sectional design of these studies [28].…”
mentioning
confidence: 99%